Adsorption and desorption of molybdenum(VI) in contaminated water using a chitosan sorbent. (June 2018) - Brion-Roby, Roxanne; Gagnon, Jonathan; Nosrati, Somayyeh; Deschênes, Jean-Sébastien; Chabot, Bruno
Graphical abstract: Highlights: A new chitosan sorbent was first explored for removal of molybdenum in water. The adsorption kinetics are very fast (less than 15 min). This sorbent possesses an adsorption capacity of 123 mg Mo g −1 at pH 7.8. The adsorption occurs through ion exchange and is best described by a Langmuir model. Dynamic studies, with BTC acquired in real-time, show a good sorbent recyclability. Abstract: This work presents a green and cost‐effective methodology for the removal of molybdate ions from aqueous solutions using an insoluble chitosan sorbent. The kinetic studies demonstrated that the adsorption was very fast (less than 15 min), representing an improvement compared to literature, and followed a pseudo-first order kinetic model. Adsorption equilibrium data were best fitted with the Langmuir model where the maximum experimental adsorption capacity was 123 mgMo  g −1 at pH 7.8. The Scatchard model showed that the sorbent was defined by more than one type of binding sites. The free energy from the Dubinin‐Radushkevich isotherm model revealed that the adsorption occurred by anion exchange. The thermodynamic results indicated that the adsorption was exothermic and was mainly controlled by enthalpic factors. The efficiency of this sorbent was more than 87% at low concentrations (e.g. 128 μg L −1 ). The breakthrough curves, described by the Thomas model, were acquired in real‐time by instrumental chromatography. The sorbent was regenerated five times with a NaCl solution with a constant adsorption capacity where a concentration factor of 4000 was achieved.